Looking-Glass Self: The Construction of Dayak Identity among Dayak Student Artists at Santo Paulus Pontianak High School - Leo Hendra; Vinco, Michael Silvester Mitchel; Romualdi, Kristoforus Bagas (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
This research aims to explain the construction of Dayak identity in students of Santo Paulus Pontianak Senior High School (SMA), who are active as ethnic Dayak artists. The research problem is that there is a lot of identity politicisation that hinders the process of equality and justice in society. Identity politicisation can be seen in general elections, regional head elections, and many mass organisations affiliated with ethnic identity. This research is a qualitative research with a looking-glass self approach from symbolic interactionism theory. The research subjects were 10 students who were active as ethnic Dayak artists. Data collection was conducted from January to March 2024. The result of the research is that the construction of Dayak identity is influenced by several things, namely (1) the influence of practical politics; (2) mystical stories; (3) the history of ethnic conflict; (4) life that depends on nature; and (5) customary law or customs. These constructions of identity contain problems, such as underutilising cultural perspectives, lacking historical breadth, and concealing the many riches of Dayak identity. This research is important to do because the politicisation of identity still occurs frequently. There needs to be an effort to understand these various identities so that identity construction is not easily trapped in pragmatic and opportunistic interests.